Proximity Effects in Mass Spectra of Benzanilides. Issue 5 (October 2021) - Fenwick, Nathan W; Saidykhan, Amie; Nazir, Yasser; Telford, Richard; Masood, Binyaameen; Martin, William H C; Gallagher, Richard T; Bowen, Richard D
The analytical value of peaks arising by a proximity effect in the electron ionization mass spectra of benzanilides has been established by examining the spectra of numerous examples of general structure XC6 H4 NHCOC6 H4 Y. Significant [M-X] + signals are observed only when X = Cl, Br, I or CH3 O in the 2-position. The presence of strong [M-X] + signals, but negligibly weak [M-Y] + peaks, even when the C-Y bond would be expected to break more readily than the C-X bond, indicates that these diagnostically useful signals do not arise by simple cleavage. Similarly, the presence of an appreciable [M-Cl] + signal, but no [M-Br] + signal, in the spectra of representative examples of 4-Br-2ClC6 H3 NHCOC6 H4 Y, reveals that loss of a substituent from the 2-position occurs much more rapidly than fission of a weaker bond to a substituent in the 4-position. These trends are interpreted in terms of cyclization of the ionized 2-substituted benzanilide, followed by elimination of the substituent originally in the 2-position, to form a protonated 2-arylbenzoxazole.